Impactos ambientais de efluentes de origem hospitalar em meio hídrico e proposta de tratamento por plasma não térmico - Rambo, Adriano Andrade (2020)
The importance of hospitals and other institutional sets of health service providers is undoubtedly deserved and of utmost need in view of the diversity of possible or unknown complications as experienced with the virus of severe acute coronavirus respiratory syndrome 2 (SARS-CoV-2), which causes the current pandemic of COVID-19. During this period we can see that many countries and regions lack progress to serve the population in a dignified and humanized way. However, care for the environment should also be taken into account and pay attention, considering that the conditions in which the environment is directly or indirectly interferes with the health of the population and the same place that treats and cures, cannot be the same that promotes diseases. In this sense, this dissertation aimed to investigate the possible environmental impacts arising from hospital waste and effluents through a current literature review of the last five years, comprising 2015 to 2019, and described in the form of an article intended for the first chapter of the dissertation. After the basic research, as a result of this, we observed in several articles the concern, mainly, in effluents and wastewater with the release, detection and quantification of antibiotics as potential causes of environmental impacts, because they interfere in the acceleration and intensify antimicrobial resistance. Thus, in order to seek a solution to eliminate antibiotics in water, for the second chapter, in article format, we aimed to investigate the degradation of the antibiotic tetracycline hydrochloride in water, fortified, through the use of non-thermal plasma (PNT), which is a clean, advanced and easy-to-apply technology. The results showed that the PNT is efficient in the degradation of tetracycline hydrochloride, presenting reductions of 91.28%, 92.19% and 93.56% in 10, 15 and 30 min of treatment, respectively. Bacterial sensitivity tests showed that antibiotic activity was inhibited in solutions that received PNT treatment for 15 and 30 minutes. However, it is considered that there is a need to monitor wastewater and hospital effluents, because they are potential routes of contamination of water bodies and derived by antibiotics; and that there are ways to treat and improve the quality of hospital effluents; that antimicrobial resistance is an extremely serious global risk that compromises people's health and the ecosystem, and tends to get worse if measures are not primarily established by decision makers.